Day of empire how hyperpowers rise to global dominance--and why they fall - Chua, Amy (Anchor Books, 2009)
In this sweeping history, bestselling author Amy Chua explains how globally dominant empires -- or hyperpowers -- rise and why they fall. In a series of brilliant chapter-length studies, she examines the most powerful cultures in history -- from the ancient empires of Persia and China to the recent global empires of England and the United States -- and reveals the reasons behind their success, as well as the roots of their ultimate demise. Chua's analysis uncovers a fascinating historical pattern: while policies of tolerance and assimilation toward conquered peoples are essential for an empire to succeed, the multicultural society that results introduces new tensions and instabilities, threatening to pull the empire apart from within. What this means for the United States' uncertain future is the subject of Chua's provocative and surprising conclusion. - Publisher.